Metagenomic and taxonomic profiling of phyllosphere bacteria from Mangifera indica in response to urban air pollutants in Medellín, Colombia - Natalia Bernal Hernández; Héctor Alejandro Rodríguez Cabal; Nancy J. Pino; Sara Ramírez Restrepo; Luisa María Múnera Porras (PLoS ONE, 2026)
Urban trees and their phyllosphere-associated microbiota constitute a promising nature-based solution for mitigating urban air pollution. In this study, we characterized the taxonomic composition, diversity patterns, and functional potential of bacterial communities inhabiting the phyllosphere of Mangifera indica in two urban sites of Medellín, Colombia, with contrasting pollution levels and across two time points, analyzing a total of 12 samples. We integrated 16S rRNA gene amplicon sequencing, performed on the Illumina MiSeq platform, with shotgun metagenomic sequencing generated on the Illumina NovaSeq 6000 platform to assess community structure and the presence of genes involved in the degradation of airborne organic pollutants. Bacterial assemblages were dominated by Pseudomonadota (Proteobacteria), Actinomycetota , and Bacteroidota, with genera such as Methylobacterium, Pseudomonas , and Serratia consistently prevalent. Alpha diversity was higher in the highly polluted downtown, while beta diversity was shaped primarily by temporal variation. Functional annotation of metagenome-assembled genomes (MAGs) uncovered genes encoding complete aromatic hydrocarbon degradation pathways, including naphthalene, toluene, xylenes, and benzoate. Both ortho- and meta-cleavage routes for catechol degradation were detected, with temporal shifts in pathway dominance linked to changes in the abundance of key degraders taxa. These results reflect genetic potential for xenobiotic degradation within the M. indica phyllosphere microbiota, modulated by environmental conditions. Our findings highlight the ecological role of phyllosphere bacteria as contributors of inferred functional capacity relevant to atmospheric bioremediation and supports their integration into microbiome-informed green infrastructure strategies.